A novel method for measuring human lipoprotein lipase and hepatic lipase activities in postheparin plasma* - S. Imamura; J. Kobayashi; K. Nakajima; S. Sakasegawa; A. Nohara; T. Noguchi; M.A. Kawashiri; A. Inazu; S.S. Deeb; H. Mabuchi; J.D. Brunzell (Journal of Lipid Research, 2008)
The objective of this study was to establish a new lipoprotein lipase (LPL) and hepatic lipase (HL) activity assay method. Seventy normal volunteers were recruited. Lipase activities were assayed by measuring the increase in absorbance at 546 nm due to the quinoneine dye. Reaction mixture-1 (R-1) contained dioleoylglycerol solubilized with lauryldimethylaminobetaine, monoacylglycerol-specific lipase, glycerolkinase, glycerol-3-phosphate oxidase, peroxidase, ascorbic acid oxidase, and apolipoprotein C-II (apoC-II). R-2 contained Tris-HCl (pH 8.7) and 4-aminoantipyrine. Automated assay of lipase activities was performed with an automatic clinical analyzer. In the assay for HL + LPL activity, 160 μl R-1 was incubated at 37°C with 2 μl of sample for 5 min, and 80 μl R-2 was added. HL activities were measured under the same conditions without apoC-II. HL and LPL activities were also measured by the conventional isotope method and for HL mass by ELISA. Lipase activity detected in a 1.6 M NaCl-eluted fraction from a heparin-Sepharose column was enhanced by adding purified apoC-II in a dose-dependent manner, whereas that eluted by 0.8 M NaCl was not. Postheparin plasma-LPL and HL activities measured in the present automated method had high correlations with those measured by conventional activity and mass methods. This automated assay method for LPL and HL activities is simple and reliable and can be applied to an automatic clinical analyzer.